A Systematic Review of Climate Change Risks to Communal Livestock Production and Response Strategies in South Africa - Zhou, Leocadia; Slayi, Mhlangabezi; Ngarava, Saul; Jaja, Ishmael Festus; Musemwa, Lovemore (Frontiers in Animal Science, 2022)
Livestock offers substantial opportunities for food security and sustainable development with appropriate adaptation to climate change. Nowadays, climate change is among the critical problems facing less privileged rural people directly depending on livestock to survive. This paper aimed to analyse the existing literature and identify knowledge gaps about climate change impacts and response strategies in rural livestock production of South Africa. The study utilized a systematic literature review with key search terms such as “climate change” (weather, variability), “livestock” (monogastric*ruminants), “impact” (heat stress; feeds; pasture; production; reproduction; health; vector-diseases), and “adaptation” (strategies; vulnerability; risks; resilience). The search was run through scientific databases such as Google scholar, Science direct, Cab direct, Sabinet and Sematic scholar, targeting titles, abstracts and keywords. From the 62 suitable peer-reviewed publications examined in the current paper, five limitations were discovered, namely: (1) limited contextual studies of South Africa’s rural livestock farming communities; (2) a silo approach to investigations on impacts and adaptation in rural livestock production; (3) drawbacks on mixed crop-livestock systems as an effective response to climate change; (4) limited studies on monogastric livestock in rural communities; and (5) geographic underrepresentation of research progress in different provinces within the country. The study recommended improving geographic coverage of literature and inclusion of non-ruminants exposed to different climatic shocks. It is further advised that to gain effective responses to climate change impacts, mitigation strategies should be context-specific and holistic to improve livestock production in rural farming communities.